Comparison of liquid-based preparation and conventional smear of fine-needle aspiration cytology of lymph node - Singh, Priya (J Cytol, 2016)
BACKGROUND: In this paper, we have compared the cytomorphologic characteristics of liquid-based preparation (LBP) [SurePath (SP)] cytology and conventional smear (CP) preparations on fine-needle aspiration (FNAC) material by a semi-quantitative scoring system for cases of lymphadenopathy. MATERIALS AND METHODS: In this prospective study, a total of 52 consecutive cases of FNAC of lymphadenopathy were included. The first pass was used for CP followed by LBP with the help of SP technique. The smears were independently compared and assessed by two observers (PS and PD). RESULTS: The semiquantitative grading was compared in two groups by Wilcoxon signed-rank test. The background information, cell architecture, pleomorphism, nuclear and cytoplasmic details, and three-dimensional structures were significantly different in LBP and CP smears. CONCLUSIONS: Liquid-based cytology (LBC) is a relatively simple technique, which exhibits good nuclear and cytoplasmic details with the absence of obscuring background material. Even the number of slides and area per slide to be screened were less than the conventional preparation but caution must be applied to interpret the slides and secure a diagnosis, especially if LBC is the first and only method applied for diagnosis.